2006
DOI: 10.1071/rd05126
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of epidermal growth factor, follicle stimulating hormone and testosterone on mouse spermatogonial cell colony formation

Abstract: The complex process of spermatogenesis is regulated by various factors. In the present study, the in vitro effects of epidermal growth factor (EGF), follicle stimulating hormone (FSH) and testosterone on spermatogonial cell colony formation were investigated, and the best colonising factor was chosen for treating cells before transplantation. Sertoli and spermatogonial cells were isolated from neonatal mouse testes. The identity of the cells was confirmed through analysis of morphology, alkaline phosphatase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…This finding is in agreement with that reported by previous studies that cultured mouse SSCs Jeong et al 2003) and SSCs in the colonies (Anjamrooz et al 2006) can result in a spermatogenesis following transplantation.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This finding is in agreement with that reported by previous studies that cultured mouse SSCs Jeong et al 2003) and SSCs in the colonies (Anjamrooz et al 2006) can result in a spermatogenesis following transplantation.…”
Section: Discussionsupporting
confidence: 95%
“…These systems include SSCs co-culture with a Sertoli cells (Anjamrooz et al 2006;Aponte et al 2006) or SIM mouse embryo-derived thioguanine-and ouabain-resistant (STO) monolayer (Kubota et al 2004a) as feeder cells, addition of serum into the culture medium , using serum-free culture medium, SSCs cultured in a potassium-rich medium called KSOM (Dirami et al 1999) and medium supplementation with various growth factors (Kanatsu-Shinohara et al 2003a, b;Kubota et al 2004b). Recently, SSCs were also isolated and cultured from adult mice (Guan et al 2006) but optimal conditions for in vitro colonization of adult SSCs is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, under the influence of EGF and FGF2, big odd-shaped colonies appeared. Stereological analysis of the colonies indicated that although EGF has been described as a spermatogonial growth factor (WahabWahlgren et al 2003, Anjamrooz et al 2006, the cultures with this growth factor showed the largest volume of somatic cells. In EGF-treated cultures, spherical colonies arose interconnected by bridges.…”
Section: Discussionmentioning
confidence: 99%
“…During spermatogenesis, Sertoli cells and reproductive hormones, such as testosterone, follicle‐stimulating hormone (FSH), and luteinizing hormone (LH), play important roles. Meanwhile, it has been reported that several cytokines, including epidermal growth factor (EGF), stem cell factor (SCF), glial derived neurotrophic factor (GDNF), and insulin‐like growth factor (IGF), were also crucial for spermatogenesis .…”
Section: Introductionmentioning
confidence: 99%